Optimization of bioactives extraction from grape marc via a medium scale ambient temperature system and stability study - Castillo, Aly; Celeiro, María; Rubio, Laura; Bañobre, Andrea; Otero-Otero, Miguel; Garcia-Jares, Carmen; Lores, Marta (Frontiers in Nutrition, 2022)
A scalable procedure with minimum energy requirements, MSAT (Medium Scale Ambient Temperature), in combination with solvents generally recognized as safe (GRAS), has been optimized to obtain polyphenolic extracts from white grape (Vitis vinifera) marc. The solvents considered were propylene glycol (Pg), ethanol (Et) and ethyl lactate (Lc), as well as their respective hydro-organic mixtures. In a first approach, the operating parameters were optimized through a response surface matrix: extractor solvent volume (range 10-150 mL), marc mass (range 20-200 g) and marc/dispersant mass ratio (range 0.5-2 g·g-1), using the total polyphenol content (TPC) and the antioxidant activity (AA) of the extracts as response parameters. The highest TPC (5918 mgGAE·L-1) and AA (44 mmolTE·L-1) values were obtained using 200 g marc and 100 mL solvent. Regarding the type of solvent, a better response was reached with Lc>Et>Pg>H2O obtaining a polyphenol concentration of 252 mg·L-1 for the hydro-organic isovolumetric ratio of ethyl lactate. In addition, the stability of the extracts was studied for 62 days. The effect of factors such as temperature, light exposure, and oxidative reactivity was evaluated. The bioactivity indices showed no changes with the storage conditions of the extracts in the first month of analysis, after which 75% of the antioxidant activity as the concentration of the polyphenolic profile (204 mg·L-1) remains. The absence of reactive oxygen and the cooling of the extract (4ºC) were the most determining factors (p<0.05) in modulating the stability of the total polyphenolic profile.